Comparison of saddle block and pudendal nerve block by SEPTA technique for anorectal surgeries: A randomized control study - Saini, Heena; Angral, Rajesh; Anshuman Mahesh Chander; Raj Rishi Sharma (Asian Journal of Medical Sciences, 2023)
Background: Simplified easily reproducible pudendal nerve block technique for anorectal surgery (SEPTA) is a novel technique of local anesthesia for anorectal surgeries. Aims and Objectives: The present study was undertaken to assess the feasibility of SEPTA technique in terms of perioperative anesthesia and patients satisfaction. Materials and Methods: A prospective, randomized, comparative single-blinded study was done with 30 patients in each of two groups. Patients in Group A received Saddle Block and in group B received pudendal nerve block by SEPTA technique. Patients were evaluated with respect to onset of anesthesia, first rescue analgesia, ambulation, and patient satisfaction scores. Statistical Analysis: Student’s independent t-test or Mann–Whitney U-test was employed for comparing continuous variables. The chi-square test or Fisher’s exact test, whichever appropriate, was applied for comparing categorical variables. Results: Onset of anesthesia was earlier (3.72±2.78 min) in Group B as compared to Group A (7.15±4.19 min). Time to first rescue analgesia was earlier in Group A (132.1±23.75 min) as compared to Group B (223.2±92.51 min). Group B patients had early ambulation (32 min) postoperatively as compared to Group A patients (297.1 min), which was statistically significant. Conclusion: SEPTA is a good alternative to Saddle Block for providing anesthesia for anorectal surgeries with added advantages of rapid onset, no risk of nausea, vomiting, back pain, urinary retention and early ambulation, and discharge of the patient.